COMPARING TOURISM COMPONENTS IN SITU BAGENDIT 1 AND 2 - Wati Susilawati; Dini Turipanam Alamanda; Tia Rosalina (Jurnal Bisnis Manajemen, 2022)
This research aims to determine the tourism components in Bagendit 1 and 2 Tourism Objects and to examine differences in tourist attractions and activities, accommodation, tourist facilities and services, transportation facilities and services, other infrastructure, and institutional elements between Bagendit 1 and 2 Tourism Objects. The research method used is a descriptive method and comparative method. The technique of collecting data was carried out through observation, interviews, and questionnaires. The sample taken was 96 respondents with unknown population formula and the sampling technique used the purposive sampling method. The data processing technique was carried out using validity tests, reliability tests and normality tests which were then processed using descriptive analysis methods and t-test differences (independent samples t-test) with the help of IBM SPSS Statistics 26. The results showed that the tourism components in Bagendit 1 and 2 Tourism Objects consisted of tourist attractions and activities; accommodation; tourist facilities and services; transportation facilities and services; other infrastructure; and institutional elements as a whole have "good" criteria with the highest average ratio owned by Situ Bagendit 1. This shows that there is a difference between Bagendit 1 and 2 Tourism Objects, namely the variables of tourist attractions and activities, tourist facilities and services, transportation facilities and services, as well as institutional elements. Meanwhile, those that show similarities between Bagendit 1 and 2 Tourism Objects are accommodation and other infrastructure variables.